Visual Perceptual Learning Induces Long-Lasting Recovery of Visual Acuity, Visual Depth Perception Abilities and Binocular Matching in Adult Amblyopic Rats - Consorti, Alan; Sansevero, Gabriele; Torelli, Claudia; Di Marco, Irene; Berardi, Nicoletta; Sale, Alessandro (Frontiers in Cellular Neuroscience, 2022)
Abnormal visual experience early in life, caused by strabismus, unequal refractive power of the eyes, or eye occlusion, is a major cause of amblyopia (lazy eye), a highly diffused neurodevelopmental disorder severely affecting visual acuity and stereopsis abilities. Current treatments for amblyopia, typically based on a penalization of the fellow eye, are only effective when applied during the juvenile critical period of primary visual cortex plasticity, resulting mostly ineffective at older ages. Here, we developed a new paradigm of operant visual perceptual learning performed under conditions of conventional (binocular) vision in adult amblyopic rats. We report that visual perceptual learning induced a marked and long-lasting recovery of visual acuity, visual depth perception abilities and binocular matching of orientation preference, providing a link between the last two parameters.